A Spatial Model of the Human Airway Tree: The Hybrid Conceptual Model - Montesantos, Spyridon; Fleming, John S.; Tossici-Bolt, Livia (Journal of aerosol medicine, 2010)
The conceptual model of the lung describes the spatial distribution of the air volume of each airway generation within the lung. It is a generic model that can be used as a powerful tool in interpreting images of aerosol deposition. The model divides the lung volume into 10 concentric shells, and specifies the volume of each airway generation in each shell based on a statistical analysis of morphometric data available in the literature. In this study, an updated version of the conceptual model, called the Hybrid Conceptual Model (HCM), is introduced. This model incorporates individual morphometric data from upper bronchial airways (generations 0-5) available from High Resolution Computed Tomography (HRCT). The HCM has been tested on one 27-year-old healthy male volunteer, on which magnetic resonance imaging (MRI) and HRCT scans of the thorax have been performed. Four major changes have been introduced in the HCM; (1) the incorporation of in vivo data, (2) a better distribution of airway volume within each shell, (3) the adoption of more accurate morphometric assumptions, and (4) the incorporation of the spatial definition of the segmental divisions of the lung. The resulting model was shown to compare very well to past literature models with respect to airway volume per generation and mean airway position within the lung. It can be concluded that the HCM can be used to describe the spatial location of different airway generations of the lung with good spatial and quantitative accuracy. This represents a further step toward the personalization of the conceptual model to an individual subject.